Understanting governance policy networks, governance, reflexivity and accountability - Rhodes, R. A. W. (Public policy and management)
Understanding Governance asks: * What has changed in British government over the past two decades, how and why? * Why do so many government policies fail? * What does the shift from government to governance mean for the practice and study of British government? This book provides a challenging reinterpretation which interweaves an account of recent institutional changes in central, local and European Union government with methodological innovations and theoretical analysis. It emphasizes: the inability of the 'Westminster model', with its accent on parliamentary sovereignty and strong executive leadership, to account for persistent policy failure; the hollowing out of British government from above (the European Union), below (special purpose bodies) and sideways (to agencies); and the need to respond to the postmodern challenge, rethinking the methodological and theoretical assumptions in the study of British government. Professor Rhodes makes a significant and timely contribution to our understanding of government and governance.